Pemberdayaan Teknik Bercerita Berbasis Budaya Bali Dalam Pembelajaran Keterampilan Menulis Karangan Pribadi Siswa Kelas V SD Mutiara Singaraja - Dibia, I Ketut; Dewantara, I Putu Mas; Widiana, I Wayan (LPPM Undiksha, 2017)
The aim of this research were to find out (1) the steps of story telling technique based Balinese culture in teaching writing pesonal story skill of fifth-grade students in SD Mutiara Singaraja, (2) studentsâ learning outcome of fifth-grade students in SD Mutiara Singaraja by empowering of story telling technique based Balinese culture in teaching writing pesonal story skill. This research was descriptive qualitative. The subject of this research were teacher and fifth-grade studentsâ of SD Mutiara Singaraja. The object of this study were the steps of story telling technique based Balinese culture in teaching writing pesonal story skill of fifth-grade students in SD Mutiara Singaraja, studentsâ learning outcome of five-grade students in SD Mutiara Singaraja by empowering of story telling technique based Balinese culture in teaching writing pesonal story skill. The data were collected by observing and testing. The result of the analysis showed that (1) the teacher did the learning activity effectively by story telling technique based Balinese culture, in preliminary, main activity , and closure, those the learning objectives could be achieved. (2) The studentsâ learning outcome of five-grade students in SD Mutiara Singaraja by empowering of story telling technique based Balinese culture in teaching writing pesonal story skill were in spendid category, that was about 93.7. Therefore, it could be concluded that the story telling technique based Balinese culture was effective to be applaid in teaching writing pesonal story skill, those the students could show the optimal learning out come.